2014
DOI: 10.9790/5736-07924552
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetric Studies on the Role of Electrode, Electrode Surface Modification and Electrolyte Solution of an Electrochemical Cell

Abstract: The present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…It is well known that for this system the kinetic parameters reported are highly variable even when using apparently identical electrodes and conditions (see [2][3][4][5][6][7][8][9][10][11][12][13][14] and references cited therein). Using our new approach we are able to show that this difficulty is not due to the impact of random experimental noise, since for each individual data set we are able to fit the mathematical model to the experimental data extremely accurately.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that for this system the kinetic parameters reported are highly variable even when using apparently identical electrodes and conditions (see [2][3][4][5][6][7][8][9][10][11][12][13][14] and references cited therein). Using our new approach we are able to show that this difficulty is not due to the impact of random experimental noise, since for each individual data set we are able to fit the mathematical model to the experimental data extremely accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, CDs/SPCE ( Figure 2 D, curve b) shows a much lower Rct value of about 27.1 kΩ, which suggested that acceleration electron transfer between the electrochemical probe [Fe(CN) 6 ] 3−/4− and electrode surface has increased due to the enhancement electrode surface area. These results can be calculated by using the Randles–Sevcik equation [ 35 ], where a CV experiment was performed in 5.0 mM Fe (CN) 6 4−/3− solution containing 0.1 M KCl at different scan rates (v) ( Supplementary Materials Figure S2 ). As a result, the electroactive surface area (A) of the bare SPCE and the CDs/SPCE electrode was determined to be 0.019 cm 2 ( Supplementary Materials Figure S2A ) and 0.054 cm 2 ( Supplementary Materials Figure S2B ), respectively, which translates to an approximately three-times improvement compared to bare SPCE ( Supplementary Materials Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…After modification of the SPCE electrode with PANI/GP composite nanofibers, the peak current increases, possibly due to the higher surface area and higher conductivities of both PANI and GP. Furthermore, the ability of diffusion control by Fe(CN) 6 3−/4− ion on the electrode surface also affected the increment in peak currents [ 46 ]. The active surface area of modified electrode shows an improvement compared to bare electrode because of the higher acceleration electron transfer of Fe (CN) 6 3−/4− ion on the roughness of the electrode surface due to the presence of PANI/GP [ 47 ].…”
Section: Resultsmentioning
confidence: 99%